Candice Lin: seeping, rotting, resting, weeping - Byers, Dan; Sung, Victoria 1987- (Carpenter Center for the Visual Arts, 2021)
Foreword / Dan Byers and Mary Ceruti -- Candice Lin : Seeping, Rotting, Resting, Weeping - materials, process, and installation -- New intimate rituals for the after times / Dan Byers -- The cats shall inherit the earth : feline portals, tactile theaters, and speculative futures / Victoria Sung -- Warty pigs, cats, and other theorists / Julia Bryan-Wilson and Mel Y. Chen -- Selected exhibitions, 2012-2021 / Liv Porte
Rückseite Titelblatt: Published on the occasion of the exhibition "Candice Lin: Seeping, Rotting, Resting, Weeping" ... Walker Art Center, Minneapolis, August 5, 2021-January 2, 2022; Carpenter Center for the Visual Arts, Harvard University, February 4-April 10, 2022
Includes bibliographical references
Keywords: Lin, Candice -- 1979-; Textilkunst; Installation -- Kunst; Keramik; Lin, Candice / Exhibitions; Art, American / 21st century / Exhibitions; Art, Modern / 21st century / Exhibitions; Imperialism in art; Exhibition catalogs; Ausstellungskatalog -- Walker Art Center -- 05.08.2021-02.01.2022 -- Minneapolis, Minn.; Ausstellungskatalog -- Carpenter Center for the Visual Arts -- 04.02.2022-10.04.2022 -- Cambridge, Mass.; Bildband